Premarital Sexual Compliance among Urban Indonesian Women: A Descriptive Study - Kristanti, Inez; Poerwandari, Elizabeth Kristi (Psychological Research on Urban Society, 2018)
Premarital sexual compliance is a common phenomenon found among women, and this tendency is influenced by the socialization of gender roles. This descriptive study examines the prevalence of and reasons for premarital sexual compliance by women in Jakarta. What surroundings are they in? What aspects of their relationships precede it? And, what are the emotional consequences of sexually compliant behavior? From 1,444 research participants obtained through accidental sampling, 391 participants have performed sexual compliance. The data for these 391 individuals was analyzed to explore and identify the intricacies of this behavior by urban women in Jakarta. Results show that gender roles and the sexual script seem to influence the occurrence of premarital sexual compliance behavior. One suggested intervention or prevention measure to eradicate this issue, among others, would be the development of a program designed to increase sexual assertiveness and to execute comprehensive sex education programs in schools.